Coronary events complicating infective endocarditis. Issue 23 (22nd June 2017) - Roux, Virginie; Salaun, Erwan; Tribouilloy, Christophe; Hubert, Sandrine; Bohbot, Yohann; Casalta, Jean-Paul; Barral, Pierre-Antoine; Rusinaru, Dan; Gouriet, Frederique; Lavoute, Cecile; Haentjens, Julie; Di Biscegli, Mathieu; et al.
Abstract : Objective: Acute coronary syndromes (ACS) are a rare complication of infective endocarditis (IE). Only case reports and small studies have been published to date. We report the largest series of ACS in IE. The aim of our study was to describe the incidence and mechanisms of ACS associated with IE, to assess their prognostic impact and to describe their management. Methods: In a bicentre prospective observational cohort study, all patients with a definite diagnosis of IE were prospectively included. The incidence, mechanism and prognosis of patients with ACS were studied. Results: Among 1210 consecutive patients with definite IE, 26 patients (2.2%) developed an ACS. Twenty-three patients (88%) had a coronary embolism. Two patients had coronary compression by an abscess or a pseudoaneurysm and one patient had an obstruction of his bioprosthesis and left coronary ostium by a large vegetation. Nineteen (73%) patients with ACS developed heart failure and this complication was 2.5 times more frequent than in patients without ACS (p<0.0001). In the ACS population, mortality rate was twice than the population without ACS. Conclusions: ACS is a rare complication of IE but is associated with an increased risk of heart failure and high mortality rate.